Card15 mutations and gastric cancer in a Portuguese population. (October 2013) - Freire, Paulo; Figueiredo, Pedro; Cardoso, Ricardo; Donato, Maria M.; Sá, Anabela; Portela, Francisco; Romãozinho, José M.; Sofia, Carlos
Abstract Background. CARD15 is involved in the innate immune response and mutations of this gene have been linked with increased risk of Crohn's disease and colorectal cancer. The relation between CARD15 mutations and gastric cancer (GC) remains controversial. Aims. To assess whether CARD15 mutations are risk factors for GC in Portugal and whether there are genotype–phenotype correlations in these patients. Methods. The 3 main CARD15 mutations (3020insC, R702W and G908R) were searched in 150 patients with GC and in 202 healthy controls. Results. Overall, CARD15 mutations were found in 28 patients (18.7%) and in 27 controls (13.4%) (p = 0.176). Individually, the incidence of 3020insC was significantly higher in patients than in controls (6.0% vs. 1.0%, p = 0.021). This polymorphism was linked with an increased risk for the intestinal-type of GC (p = 0.002), while no association was found with the diffuse and/or mixed types. Genotype frequencies for R702W (10.0% vs. 7.9%) and G908R (4.0% vs. 4.0%) were not statistically different between the two groups. Similarly, no significant associations were detected between these two polymorphisms and the different histological GC types. No correlations were observed between CARD15 mutations and family history, mean age at diagnosis or GC stage. Conclusions. The CARD15 3020insC variant is a risk factor for intestinal GC in Portugal. CARD15 variants are not correlated with age of diagnosis or family aggregation of the disease neither with the GC stage.